2008
DOI: 10.4049/jimmunol.180.1.269
|View full text |Cite
|
Sign up to set email alerts
|

Induction and Evolution of Cytomegalovirus-Specific CD4+ T Cell Clonotypes in Rhesus Macaques

Abstract: CMV infection induces robust CD4+ T cell responses in immunocompetent hosts that orchestrate immune control of viral replication, dissemination, and disease. In this study, we characterized the clonotypic composition of CD4+ T cell populations specific for rhesus CMV (RhCMV) in chronically infected adult rhesus macaques (RM) and in juvenile RM undergoing primary RhCMV infection and subsequent secondary challenge with RhCMV. In adult RM with established chronic infection, RhCMV-specific CD4+ T cell populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 55 publications
6
28
1
Order By: Relevance
“…Similar divergent kinetics of CD8 T cells were also described in BALB/c mice (34) as well as in HCMV infection where HCMV-specific CD8 T cell frequencies are highly increased in elderly compared with young individuals (35,36). With respect to CMV-specific CD4 T cell dynamics, data from human as well as rhesus macaque studies also indicated an "inflationary" behavior of CMV-specific CD4 T cells in seropositive individuals during latent stages of infection (37,38).…”
Section: Discussionsupporting
confidence: 52%
“…Similar divergent kinetics of CD8 T cells were also described in BALB/c mice (34) as well as in HCMV infection where HCMV-specific CD8 T cell frequencies are highly increased in elderly compared with young individuals (35,36). With respect to CMV-specific CD4 T cell dynamics, data from human as well as rhesus macaque studies also indicated an "inflationary" behavior of CMV-specific CD4 T cells in seropositive individuals during latent stages of infection (37,38).…”
Section: Discussionsupporting
confidence: 52%
“…The clonotypic composition of the human pp65-specific CD4 ϩ T-cell repertoire has also been shown to be extremely restricted and stable (23). Similarly, clonal restriction has been noted in the rhesus macaque cytomegalovirus (RhCMV) model (204), whereby the presence of a highly polyclonal RhCMV-specific CD4 ϩ T-cell population during primary infection was followed by a narrowing of the antigen-specific clonotypic repertoire in the chronic phase. Interestingly, challenge with RhCMV instigated the reemergence and dominance of RhCMV-specific CD4 ϩ T-cell clonotypes that were detected only during the acute phase of infection.…”
Section: Ii) Cd4 ؉ T Cells While the Role Of The Major Histocompatibmentioning
confidence: 94%
“…Our previous studies have noted infrequent and low levels of shedding of 68-1 following either intravenous or subcutaneous inoculation, far below the levels seen in naturally infected monkeys (1,37,78,79). Others have noted relatively high titers of 68-1 in saliva following inoculation of either RhCMV-seronegative or -seropositive macaques, as well as the recovery of virus in urine (33,35,56). The reasons for differences in the quantifications of RhCMV 68-1 genomes in mucosal fluids between different groups is not known and may be related to differences in methodologies.…”
Section: Discussionmentioning
confidence: 99%